2005
DOI: 10.4049/jimmunol.175.4.2091
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT Cells Exacerbate Type 1 Diabetes Induced by CD8 T Cells

Abstract: Invariant NKT (iNKT) cells have been implicated in the regulation of autoimmune diseases. In several models of type 1 diabetes, increasing the number of iNKT cells prevents the development of disease. Because CD8 T cells play a crucial role in the pathogenesis of diabetes, we have investigated the influence of iNKT cells on diabetogenic CD8 T cells. In the present study, type 1 diabetes was induced by the transfer of CD8 T cells specific for the influenza virus hemagglutinin into recipient mice expressing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
3
16
2
1
Order By: Relevance
“…In contrast, NKT cells enhanced the activation and expansion of diabetogenic CD8 ϩ T cells, and their differentiation into effector cells producing IFN-␥, exacerbating the development of diabetes (46). Combined with our results, this suggests that NKT cells regulate immune responses in vivo by enhancing or suppressing the activation and proliferation of CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, NKT cells enhanced the activation and expansion of diabetogenic CD8 ϩ T cells, and their differentiation into effector cells producing IFN-␥, exacerbating the development of diabetes (46). Combined with our results, this suggests that NKT cells regulate immune responses in vivo by enhancing or suppressing the activation and proliferation of CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 62%
“…Third, NKT cells might be differentially involved in the regulation of the secondary immune response of different subsets of immune effector cells. In this context, Griseri and colleagues (27) showed that adoptive transfer of islet-specific CD8 + T cells into NKT cell-enriched Va14 + transgenic recipients exacerbated type I diabetes. They also showed that NKT cells impaired the differentiation of anti-islet CD4 + T cells into Th1 effector cells, and that eventually the autoreactive CD4 + T cells become anergic (28 …”
Section: Compared With Cd1dmentioning
confidence: 99%
“…Enquanto muitos autores concordam que as células TNK contribuem para a prevenção das doenças auto-imunes, a exemplo do DM1, pelo menos em modelo de camundongos NOD, nos quais exercem uma complexa regulação da resposta imune (44)(45)(46)(47), outros estudos referem que estas células não interferem com a doença (48) ou que podem contribuir para o agravamento da mesma (49).…”
Section: Hipótese Da Higiene / Mecanismos Regulatórios Da Resposta Imuneunclassified